2018
DOI: 10.1101/378778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene expression profiling of The Cancer Genome Atlas supports an inverse association between body mass index (BMI) and major oesophageal tumour subtypes

Abstract: In the last decade the Cancer Genome Atlas (TCGA) program has revealed significant insights into molecular events of dozens of cancers. These data sets are continuously updated, providing an unprecedented resource to the research community. There is now an emerging link between obesity and the development and progression of cancer. In this study we wished to identify genes related to body mass index (BMI) in TCGA datasets. Supporting epidemiological data, our gene expression profiling analyses suggest that oes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The trans gene SYNC was found to interact with dystrobrevin (DMD gene) in order to maintain muscle function (during contraction) in mice as well as being associated with neuromuscular disease [134,135]. In addition, in Seim et al (2018) [136], the authors investigated the relationship between obesity and cancer subtypes and found that PHETA1/FAM109A expression is associated with body mass index (BMI) in esophageal carcinoma in data from The Cancer Genome Atlas (TCGA). PHOSPHO1 has been found to be involved in metabolism, specifically in energy homeostasis [137] and has also been associated via DNA methylation with BMI [138] and HDL levels, which in turn have been negatively associated with LBM [139].…”
Section: Application To Gtex Skeletal Muscle Tissuementioning
confidence: 99%
“…The trans gene SYNC was found to interact with dystrobrevin (DMD gene) in order to maintain muscle function (during contraction) in mice as well as being associated with neuromuscular disease [134,135]. In addition, in Seim et al (2018) [136], the authors investigated the relationship between obesity and cancer subtypes and found that PHETA1/FAM109A expression is associated with body mass index (BMI) in esophageal carcinoma in data from The Cancer Genome Atlas (TCGA). PHOSPHO1 has been found to be involved in metabolism, specifically in energy homeostasis [137] and has also been associated via DNA methylation with BMI [138] and HDL levels, which in turn have been negatively associated with LBM [139].…”
Section: Application To Gtex Skeletal Muscle Tissuementioning
confidence: 99%